Use the backbone of your samples: fish vertebrae reduces biases associated with otoliths in seabird diet studies - Alonso, Hany (2013)
A literature review showed that most recent conventional dietary studies of Procellariiformes have used otoliths alone to identify fish prey. Using data from a dietary study of Cory’s Shearwaters Calonectris diomedea, based on 673 regurgitates from adult birds, we quantitatively compared the contribution of otoliths and vertebrae for prey identification and quantification. By using otoliths alone, the importance of the main fish prey was greatly underestimated and several species would have been considered completely absent. Therefore, we strongly recommend the combined use of vertebrae, otoliths and other fish remains in order to improve the quality of dietary studies of seabirds.